2022
DOI: 10.1186/s12909-022-03205-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on ophthalmology resident surgical experience: a retrospective cross-sectional analysis

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic caused significant disruption to in-office and surgical procedures in the field of ophthalmology. The magnitude of the impact of the pandemic on surgical training among ophthalmology residents is not known. This study aims to quantify changes in average case logs among United States (U.S.) ophthalmology residency graduates prior to and during the COVID-19 pandemic. Methods Retrospective, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
3
3
0
Order By: Relevance
“…On the other hand, Vongsachang et al investigated the impact of the COVID-19 pandemic on ophthalmology residency training in the USA 14. The study included 195 ophthalmology residents who completed an online survey, and similar to our findings, the results showed that the pandemic had a significant impact on their training, particularly in terms of surgical volume and case diversity.…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, Vongsachang et al investigated the impact of the COVID-19 pandemic on ophthalmology residency training in the USA 14. The study included 195 ophthalmology residents who completed an online survey, and similar to our findings, the results showed that the pandemic had a significant impact on their training, particularly in terms of surgical volume and case diversity.…”
Section: Discussionsupporting
confidence: 77%
“…This is similar to stable case volumes noted in trainee case logs including urology residents, Society of Urologic Oncology fellows, and general surgery residents 10–12 . However, for some surgical specialties, there were significant decreases in volume including ophthalmology and otolaryngology 13,14 . This may reflect differences in the proportion of elective cases as well as the relative risk of COVID‐19 transmission during the procedures.…”
Section: Discussionsupporting
confidence: 62%
“…[10][11][12] However, for some surgical specialties, there were significant decreases in volume including ophthalmology and otolaryngology. 13,14 This may reflect differences in the proportion of elective cases as well as the relative risk of COVID-19 transmission during the procedures. For urology FPMRS fellows, there was a statistically significant decrease among two COVID-affected cohorts: GI procedures decreased for AY 2020−2021 from AY 2019−2020 (4.2 vs. 8.9, p = 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Surgical logs of trainees in the United States also showed a significant dip in the number of surgeries performed or assisted in 2020–2021 as compared to the previous years. [ 3 ]…”
mentioning
confidence: 99%